The influence of antineoplastic treatment on the weight of survivors of childhood cancer - Julia Ferrari Carneiro Teixeira; Priscila dos Santos Maia‐Lemos; Mônica dos Santos Cypriano; Luciana Pellegrini Pisani (Brazilian Society of Pediatrics, 2016)
Purpose: Obesity is a late effect in survivors of childhood cancer and correlates with chronic complications. Survivors of leukemia, brain tumors, and hematopoietic stem cell transplantation are more likely to develop obesity resulting from treatment modalities such as radiotherapy and glucocorticoids. This paper analyzes and integrates the current data available to health professionals in order to clarify strategies that can be used to treat and prevent obesity in childhood cancer survivors. Sources: This is a literature review from on scientifically reliable electronic databases. We selected articles published in the last five years and earlier articles of great scientific importance. Data synthesis: The mechanisms involved in the pathophysiology of obesity in cancer survivors are not completely understood, but it is believed that damage to the hypothalamus and endocrine disorders such as insulin resistance, leptin resistance, and hormone deficiency may be involved. The body composition of this group includes a predominance of adipose tissue, especially in those undergoing hematopoietic stem cell transplant and total body irradiation. The use of body mass index in these patients may lead to an underestimation of individuals risk for metabolic complications. Conclusion: Early identification of groups using accurate anthropometric assessments, interventional treatment, and/or preventative measures and counseling is essential to minimize the adverse effects of treatment. Physical activity and healthy eating to promote weight loss in the whole population should be encouraged.